EFEKTIVITAS CAISIN SEBAGAI TANAMAN PERANGKAP PATOGEN UNTUK PENGENDALIAN PENYAKIT AKAR GADA PADA KUBIS - . Hadiwiyono; . Sholahuddin; Endang Sulastri (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
he research was conducted by observation on 5 plot kinds of cabbage planting. The plots consist of control plot with no planting Chinese cabbage, plot with planting Chinese cabbage as rotation plant on 38 day before planting of cabbage followed by manual eradication, plot with planting Chinese cabbage as rotation plant on 38 day followed by flooding for 14 days and soil tillage, plot with mixcropping Chinese cabbage on the early growth stage of the cabbage, and plot with intercropping of Chinese cabbage on 14 days before planting the cabbage. The results showed that planting Chinese cabbage as trap crop of the pathogen followed by eradication of the infected Chinese cabbage effectively controlled clubroot intensity and significantly restored the partial yields of the cabbage.